Factors Associated With and Barriers to Disclosure of a Sexual Assault to Formal On-Campus Resources Among College Students. (February 2021) - Mennicke, Annelise; Bowling, Jessamyn; Gromer, Jill; Ryan, Clare
Sexual assault on college campuses occurs at high rates, but disclosure to formal on-campus resources remains low. This study used a mixed methodological survey to explore demographic and social characteristics of students who formally reported their assaults and those who did not and examined barriers to formal disclosure. Responses revealed that students who disclosed to formal on-campus resources suffered frequent polyvictimization, had high rates of physical and emotional consequences, and were mostly White women involved in campus organizations. Barriers to formal resource utilization were identified at the individual, interpersonal, organizational, and community levels.